The Influence of Digital Marketing, Word of Mouth, and Quality of Service on Patients' Decisions to Visit Budi Medika Hospital Bandar Lampung - Luther Theng; Bobby Wiryawan Saputra (International Journal of Science and Society, 2023)
In the current era, hospitals face intense competition. To increase patient interest in visiting the hospital, marketing media is needed. One of the marketing media is Digital Marketing, apart from that, communication media for exchanging information is also needed through word of mouth where the experience of patients who have used services regarding the good quality of hospital services is very important. This research aims to determine and analyze the role of digital marketing, word of mouth, and service quality on patients' decisions to visit Budi Medika Hospital Bandar Lampung. This research was carried out using a quantitative approach. The sampling technique is accidental sampling with a cross-sectional method. Data analysis in this research uses multiple linear regression analysis using SPSS 29. The results of multiple linear regression show that the variables digital marketing, word of mouth, and service quality have a positive and significant effect, both partially and simultaneously, on the decision to visit. This then shows that the higher the digital marketing, word of mouth, and service quality, the higher the decision to visit.